2016
DOI: 10.1103/physrevlett.116.073901
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excitation of an Inner-Shell Electron by Laser-Induced Electron Recollision

Abstract: Extreme ultraviolet attosecond pulses, generated by a process known as laser-induced electron recollision, are a key ingredient for attosecond metrology, providing a tool to precisely initiate and probe subfemtosecond dynamics in atoms, molecules, and solids. However, extending attosecond metrology to scrutinize the dynamics of the inner-shell electrons is a challenge, that is because of the lower efficiency in generating the required soft x-ray (ℏω>300  eV) attosecond bursts. A way around this problem is to u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The interaction of atoms and molecules with intense lasers is a key for a rich set of physical phenomena associated with attosecond physics processes such as high harmonic generation [1][2][3][4] (HHG), above threshold ionization [5] (ATI), laser induced diffraction imaging [6] (LIED), laser induced innershell excitation [7,8] and steering electrons in molecules [9]. The simple-man model, known also as the three-step-model [10,11] is a good starting point to gain an insight into these high-field processes.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of atoms and molecules with intense lasers is a key for a rich set of physical phenomena associated with attosecond physics processes such as high harmonic generation [1][2][3][4] (HHG), above threshold ionization [5] (ATI), laser induced diffraction imaging [6] (LIED), laser induced innershell excitation [7,8] and steering electrons in molecules [9]. The simple-man model, known also as the three-step-model [10,11] is a good starting point to gain an insight into these high-field processes.…”
Section: Introductionmentioning
confidence: 99%
“…Only a linear or slightly elliptical laser field can force an ionized electron to return to the molecular ion with a significant kinetic energy. The resulting recollision is at the origin of many physical processes such as HHG [15,16], nonsequential double ionization [17], molecular fragmentation [18], formation of high-order Rydberg atoms [19], and inner-shell electronic excitation of molecules [20].…”
mentioning
confidence: 99%
“…Depending on the energy that the electron transfers, a second electron may be directly knocked out, resulting in nonsequential double ionization [7,[12][13][14], or be pumped to some excited states which will be subsequently tunneling ionized by the field [15,16]. Recently, Deng et al further demonstrated inner-shell excitation by rescattering followed by x-ray emission [17]. In molecules, the rescattering electron may excite the parent molecular ion to repulsive states, thus initiating molecular dissociation or Coulomb explosion [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%